Application of ELECTRE method in business strategic planning: analysis of development, diversification, and market expansion alternatives - Setyawan, Bayu; Sapuguh, Iman; Ahlina, Nur; Wahyudi, Agung; Rosalinda, Adinda Sandra (Institute of Computer Science (IOCS), 2024)
This research applies the ELECTRE Method in the analysis of PT Djarum's business strategic planning, focusing on business development, product diversification, and market expansion. Using three main criteria with assigned weights, this study evaluated five strategic alternatives. The results show that New Business Development (PBB) dominates the ranking with the highest Net Flow, signaling high conformity with the criteria and weights. Product Diversification (DP) follows as a viable alternative, while Global Market Expansion (EPG), Strategic Partnership (KS), and Regional Market Expansion (EPR) are ranked according to their respective suitability levels. These conclusions provide strong strategic guidance for PT Djarum in making informed business decisions and support the long-term growth and sustainability of the company amidst the changing dynamics of the competitive cigarette industry.